Variables cognitivas y metacognitivas en la comprensión de textos científicos: el papel de los esquemas y el control de la propia comprensión - Otero, J. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This paper tries to apply some models and results of psychological research on comprehension processes to the learning of scientific texts. More specifically, the role of the learner's schemes and control over self -comprehension when processing a scientific text is studied.